Should Rural Gifted Education Be Different? A Survey of Teacher Educators - Kay Sather Bull; Anne Fishkin (Journal of Research in Rural Education, 1987)
Gifted education is not provided in many rural schools. Some teacher educators believe that one of the reasons for this is that gifted teachers and gifted teacher training programs are oriented to provide education applicable only to urban and suburban settings. This paper presents the results of a survey of representatives of teacher training institutions offering gifted education programs. The group surveyed was derived from the list developed by Parker and Karnes [61. Each respondent was asked to indicate whether or not differentiation of gifted teacher education for rural gifted teachers was necessary. More than 60010 of the respondents believed that differentiation was necessary. All areas surveyed, e.g., teaching methods, program development, guidance counseling, underachievement, identification practices, program administration and evaluation, etc., were candidates for differentiation with the greatest need being in the areas of program development, curriculum development, and identification.